Surface Roughness Effect on Discharge Coefficient of Combined Cylindrical Weir Gate Structure - Jalil, Shaker A.; Ibrahim, Safa S. (Science Journal of University of Zakho, 2015)
The aim of this research is to investigate the effect of surface roughness on the performance of weir and gate. An experimental study in a laboratory ﬂume is carried out to study flow over and under cylindrical weir gate in combined structure as flow measurement device. Four models having different diameters were tested in a laboratory flume. In each model, the surface was roughed four times. The results of the test show logical negative effect of the increase of surface roughness on the performance. The performance of the combined structure improved with decrease ratio of roughness to the upstream head (Ks/H) and with the increase of the total head to the diameter of the weir (H/d). Empirical relations were obtained to estimate the variation of discharge coefficient (Cd) in terms of some dimensionless parameters. Within the limitations of the present experimental work an equation to predict the discharge is proposed with R2 of 0.936. Finely the contribution of the gate increases relative to the weir when the surface roughness increases.